A needle in the haystack-Looking for the lost Wells tree. Issue 1 (2nd January 2021) - Frost, Andrew; Lethbridge, Mark
ABSTRACT: In 1891, three members of the Elder Scientific Expedition, led by Lawrence Wells O.B.E., undertook two exploratory traverses while the main party was travelling through the Far North West of South Australia. Following the common practice of the day at the southern apex of each traverse, Wells blazed his initials and date on a tree. One of these trees is known, with the westernmost having not been seen again until it was thought to have been found in 2005 when a search party found a tree with a partially healed scar. Wells was an accomplished surveyor and followed the common practice of the times by recording relatively precise latitude readings, but not longitude. While the route the main party took is well documented and well known, this second traverse is unknown. To recreate the route Wells took and provide some probability as to the location of this tree, a more novel approach was required. Specialist spatial software was developed for this study that compares the elevations and distances between sand ridges meticulously recorded by Wells, enabling recreation of his traverse, providing some certainty as to the location of this remote tree.